Macroscopic cartilage repair scoring of defect fill, integration and total points correlate with corresponding items in histological scoring systems – a study in adult sheep. Issue 4 (April 2017) - Goebel, L.; Orth, P.; Cucchiarini, M.; Pape, D.; Madry, H.
Summary: Objective: To correlate osteochondral repair assessed by validated macroscopic scoring systems with established semiquantitative histological analyses in an ovine model and to test the hypothesis that important macroscopic individual categories correlate with their corresponding histological counterparts. Methods: In the weight-bearing portion of medial femoral condyles ( n  = 38) of 19 female adult Merino sheep (age 2–4 years; weight 70 ± 20 kg) full-thickness chondral defects were created (size 4 × 8 mm; International Cartilage Repair Society (ICRS) grade 3C) and treated with Pridie drilling. After sacrifice, 1520 blinded macroscopic observations from three observers at 2–3 time points including five different macroscopic scoring systems demonstrating all grades of cartilage repair where correlated with corresponding categories from 418 blinded histological sections. Results: Categories "defect fill" and "total points" of different macroscopic scoring systems correlated well with their histological counterparts from the Wakitani and Sellers scores (all P  ≤ 0.001). "Integration" was assessed in both histological scoring systems and in the macroscopic ICRS, Oswestry and Jung scores. Here, a significant relationship always existed (0.020 ≤  P  ≤ 0.049), except for Wakitani and Oswestry ( P  = 0.054). No relationship was observed for the "surface" between histology and macroscopy (all P  > 0.05). Conclusions: Major individual morphological categories "defect fill" and "integration", and "total points" of macroscopic scoring systems correlate with their corresponding categories in elementary and complex histological scoring systems. Thus, macroscopy allows to precisely predict key histological aspects of articular cartilage repair, underlining the specific value of macroscopic scoring for examining cartilage repair.